Antithrombin III Avranches, a New Variant with Defective Serine-Protease Inhibition - Comparison with Antithrombin III Charleville - Aiach, M; Roncato, M; Chadeuf, G; Dezellus, P; Capron, L; Fiessinger, J N (Thrombosis and Haemostasis, 1988)
A decreased plasma antithrombin activity in presence or in absence of heparin was discovered in a 47-year-old patient presenting with recurrent venous thromboembolism. The immunoreactive material (AT ΠΙ-IR) was normal. The same biological abnormalities were found in two relatives of the patient, leading to the diagnosis of hereditary qualitative AT III deficiency.The propositus’ AT III was coeluted with normal AT III from an heparin-sepharose column. An additional step of ion-exchange chromatography on a Mono Q column using a FPLC system (Pharmacia, St-Quentin en Yvelines, France) allowed the purification of a protein which was homogenous in SDS-10% polyacrylamide electrophoresis gel (PAGE). AT III purified from propositus’ plasma, normal plasma and the plasma of the patient known to have an AT III variant with defective protease binding (AT III Charleville) were compared. The specific activities measured as heparin cofactor anti thrombin or factor Xa inhibition in absence of heparin were decreased to half the normal value.Kinetic studies confirmed a decreased rate of thrombin inhibi-tion for both abnormal AT III preparations. SDS-PAGE experi-ments performed in purified system and immunoblots obtained from plasma showed that the two variants have different behaviour: in the case of AT III Charleville thrombin induced an apparent 5 Δ increase in molecular mass, probably due to a conformational change. AT III Avranches did not form stoechiometric complexes with thrombin, but was unmodified by the protease.
Keywords: AT III; Variant; Serine-protease binding site